No Evidence for Individual Assortment by Temperament Relative to Patch Area or Patch Openness in the Bobolink. - Reed, J. Michael.; Keyel, Alexander C.; Peck, David T. (Tufts University. Tisch Library., 2016)
Recent research has shown repeatable individual variability in temperament traits. We tested the hypotheses that individual Bobolinks (Dolichonyx oryzivorus) vary consistently in their response to predators, a temperament trait, and that this individual variation is associated with breeding-site selection. Specifically, we tested whether measures of behavioral response to human approaches are associated with either patch area or patch openness and thus to area sensitivity. We made two to seven sequential approaches to Bobolinks in 2009 and 2010, measuring starting distance, flight-initiation distance, and the distance from the observers to where the birds landed. We analyzed the data with repeatability estimates and linear mixed modeling. Flight-initiation distance was repeatable when starting distance was controlled for, but distance to landing was not after starting distance and flight-initiation distance were controlled for. We found no strong effect of area or openness on either flight-initiation distance or distance to landing. We conclude that this measure of response to predators shows individual variation, but this variation does not explain patterns of settlement among habitat patches. Because flight-initiation distance is often used to identify distances at which human behavior disrupts wildlife, we estimate its mean (21.8 m) and the distance at which 75%, 95%, and 99% of the Bobolinks flushed (28, 40, and 59 m, respectively)